Effect of polyacrylamide on compression rate of lime stabilized soil - Gao, Mingxing; Yuan, Feilong; Xue, Yanhua; Peng, Guan (Penerbit Universiti Kebangsaan Malaysia, 2020)
In order to explore the influence mechanism of polyacrylamide on the compressibility of lime-stabilized soil, polyacrylamide with different contents was added to lime-stabilized soil, and the relationship between the consolidation coefficient and the consolidation pressure was obtained through one-dimensional laboratory consolidation experiment, and samples were taken for nitrogen adsorption experiment and observation with solid microscope. The results show that the microscopic image shows that the reaction of polyacrylamide with lime will form a spatial network structure; 0.24% polyacrylamide can effectively reduce the compression of lime stabilized soil, and the porosity ratio of solidified soil can be increased by 15.4%, and the consolidation rate can be accelerated by 413.2%. The pore volume distribution shows that the addition of polyacrylamide to lime stabilized soil can reduce the mesopore volume of the solidified soil and produce ultra-large pores. At the same time, the porosity ratio of the solidified soil is increased, which is beneficial to the drainage of super-pore water in the soil, accelerate the consolidation rate of solidified soil, shortens the time of consolidation and stability of the soil.